Environmental Interpretation based on the principles of Behavior Analysis: contributions to Environmental Education - Medeiros, Diego Marques da Silva; Haydu, Verônica Bender (Perspectivas em Análise do Comportamento, 2018)
This essay discusses the definition, objectives and results of Environmental Interpretation (EI) from an analytical-behavioral view to provide researchers, planners and practitioners of EI, and behavior analysts an alternative of scientific research related to environmental interpretation. For such, the essay presents: (a) some principles and concepts of behavior analysis (BA); (b) the definition of EI in parallel to concepts of BA; (c) the specific objectives of EI based on the principles of BA. BA is the science that studies human behavior through functional analysis in the contexts in which they occur. Parallel to the principles of BA, EI can be understood as an activity that seeks contextual understanding of the individual about the environment, so that the subject constructs meanings that are adequate for conservation of the patrimony it visits. In turn, Environmental Education has broader objectives, not achievable within the spatial and temporal limits of EI. Finally, it is suggested that BA provides principles and methods relevant to the study and execution of EI, and also that EI is a vast and unprecedented field of applied research for behavior analysts to explore.